2018
DOI: 10.1017/s0022149x18000305
|View full text |Cite
|
Sign up to set email alerts
|

Development ofPhasmarhabditis hermaphrodita(and members of thePhasmarhabditisgenus) as new genetic model nematodes to study the genetic basis of parasitism

Abstract: The genetic mechanisms of how free-living nematodes evolved into parasites are unknown. Current genetic model nematodes (e.g. Caenorhabditis elegans) are not well suited to provide the answer, and mammalian parasites are expensive and logistically difficult to maintain. Here we propose the terrestrial gastropod parasite Phasmarhabditis hermaphrodita as a new alternative to study the evolution of parasitism, and outline the methodology of how to keep P. hermaphrodita in the lab for genetic experiments. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 85 publications
3
46
0
Order By: Relevance
“…Wales (Andrus & Rae, 2018). Our strain was isolated from a snail (Oxychilus draparnaudi) collected from Pembrokeshire, Wales (Andrus & Rae, 2018). Research into P. californica has concentrated on its recent description (Tandingan de Ley et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wales (Andrus & Rae, 2018). Our strain was isolated from a snail (Oxychilus draparnaudi) collected from Pembrokeshire, Wales (Andrus & Rae, 2018). Research into P. californica has concentrated on its recent description (Tandingan de Ley et al…”
Section: Discussionmentioning
confidence: 99%
“…Wild strains of Phasmarhabditis were sub-cultured by growing them in White traps (described in Andrus & Rae, 2018) where approximately 100 nematodes were added to a rotting piece of Limax flavus and left for 28 days until they grew to the dauer stage and then used in experiments. For each snail species three replicate plates were used and the experiment was repeated three times.…”
Section: Chemotaxis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, phoretic associations between Pristionchus pacificus and scarab beetles (Herrmann et al, 2006), Caenorhabditis japonica and the shield bug Parastrachia japonensis (Kiontke et al, 2002;Tanaka et al, 2010), and the facultative parasite Phasmarhabditis hermaphrodita and slugs of the genus Arion or Deroceras as well as the snail Helix aspersa (Rae et al, 2009;Félix et al, 2018;Andrus & Rae, 2019). Previous studies have shown that mucus of the slug Arion subfuscus and the snail Helix aspersa act as strong chemoattractants for P. hermaphrodita (Rae et al, 2009;Andrus & Rae, 2019). This association with slugs and snails has also been observed with C. elegans, where nematodes have been recovered from the intestines and feces of Arion sp.…”
Section: Introductionmentioning
confidence: 99%
“…Imagine a world where the discoveries of RNAi, the genetic regulation of apoptosis and the development of GFP (green fluorescent protein) that resulted in 3 Nobel prizes were due to studying the slug parasite P. hermaphrodita rather than C. elegans! Recently, P. hermaphrodita has been proposed as a model system of its own -specifically to study the evolution of parasitism (Wilson et al, 2015;Rae, 2017a;Andrus and Rae, 2018). Several attributes make it a perfect system and recently protocols have been developed that show how to culture it under lab conditions, mutagenize, mate and make isogenic lines of P. hermaphrodita just like C. elegans (Andrus and Rae, 2018).…”
mentioning
confidence: 99%